Connecting and Disconnecting: Exploring Prisoners' Relations with the Outside World in Myanmar. Issue 1 (1st March 2020) - Jefferson, Andrew M.; Martin, Tomas Max
Abstract: Drawing on a case study carried out in Myanmar, this article elaborates on the concept of connectivity as a rich and critical articulation of the way prisoners and their relatives develop and sustain relationships during incarceration. The notion of connectivity offers an alternative analytic frame to that provided by established notions of prisoner–family contact. Drawing primarily on interview data, we examine how people connect and disconnect in situations of chaos, control and surveillance; how they suffer under circumstances of not-knowing; and how they establish protective exchange relations. We illustrate the utility of the concept of connectivity for interrogating the fundamentally relational practice of imprisonment and show that common notions of inside and outside are partially deconstructed through prison actors' agentic efforts to cut ties or tie strings across prison walls.